Financial inclusion, innovation, and investments biotechnology and capital markets working for the poor - Christy, Ralph D.; Bogan, Vicki L. (World Scientific Pub. Co., 2011)
This book is a state-of-the-art discussion of what has succeeded (and failed) in the design and implementation of projects and institutions to assist the poor in developing country economies. In Africa especially, far too many people are still living under conditions of extreme poverty. The goal of the book is twofold : (1) to identify and assess the key processes through which markets affect the livelihoods of the rural poor; and (2) to propose micro- and macro-level policies and innovations to address the problems of inclusion that arise. Featuring contributions from leading scholars and professionals in the field, this volume is timely to all those involved in designing innovative institutions that transfer capital and technologies to low-income countries facing the challenges of poverty alleviation and economic development.